Eastern Region Transport Survey Volume IV Part II: Highways and Highway Transport (Appendices) - Planning Commission (Planning Commission, 1967)
The "Chief Engineer (Roads and adding's)" is responsible for the construction and maintenance of all roads and buildings under State jurisdiction. There are no other Chief Engineers or Additional Chief Engineers. He supervises directly the six Superintending Engineers under him.
Regional Transport Survey Unit Eastern Region, Calcutta Planning Commission
Government of India